The daily value of micronutrients in newly produced beef and horse concentrated bone broths (Mongolian Journal of Agricultural Sciences, 2018)
Beef and horse marrow bones were used to produce the concentrated bone broth and the possibility to make a bone broth only with salt was assessed. Protein and mineral contents in horse broth were higher (p＜0.02; 1.92 and 2.3%, respectively) than in beef broth. Concentrions of calcium, magnesium and iron in beef bone broth (85.3, 46.7 and 23.3 mg/100g) were higher (p